Does Attractiveness Lead to or Follow From Occupational Success? Findings From German Associational Football. (January 2020) - Meier, Henk Erik; Mutz, Michael
Prior research has provided evidence that attractiveness is associated with work-related advantages. It is less clear, however, whether attractiveness is an antecedent or a consequence of professional success. To answer this question, associational football in Germany is used as an exemplifying case. Portrait pictures of German football players were retrieved, one picture from a very early career stage and one from a very late one. Attractiveness of these portraits was assessed by the "truth of consensus" method. Panel regression models are applied to analyze changes in attractiveness and relate these changes to professional success. Findings show that success as a footballer cannot be predicted with attractiveness at early career stages. Instead, the increase of attractiveness over time is more pronounced among very successful players. It is thus concluded that successful individuals are not more attractive in the very beginning, but improve their appearance throughout their careers.